Analisis Keterlaksanaan Kurikulum Merdeka dalam Pembelajaran Biologi di SMA Negeri 3 Majene - Janadwiyani, Janadwiyani; SY, Nursyamsi; Pujiastuti, Indah Panca; Nur, Syamsiara; Aslam, Muhammad (Journal of Health, Education, Economics, Science, and Technology, 2025)
The Merdeka Curriculum is a curriculum with diverse intracurricular learning, where students have sufficient time to explore concepts and strengthen competencies. The purpose of this research is to know the planning, implementation and evaluation of the Merdeka Curriculum at SMAN 3 Majene. The approach used in this research is qualitative. The research subjects consisted of the head of school, deputy head of the curriculum department, biology teacher and student of SMAN 3 Majene. The research data is collected through observations on learning in class, interviews and queries. The data is analyzed using techniques of qualitative analysis in descriptive terms, including data collection, data reduction, data presentation, and conclusion drawings. This research indicates that the planning, implementation and evaluation stage of the implementation of the Merdeka Curriculum at SMAN 3 Majene has gone well through differential learning that is always tailored to the needs and interests of learners. Although there are still some obstacles, schools are always trying to overcome them. It is hoped that this inspection can be a reference to further study of ICTs, the obstacles faced and the solutions that can be provided.